PENGARUH PEMBERIAN KOMPOS BLOTONG LIMBAH PABRIK GULA DAN MIKORIZA TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (ELAEIS GUINEENSIS JACQ) - Sari, Kartika; Wahyuni, Mardiana; Wijaya, Hardy (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2019)
Nursery success is one of the important things in the oil palm plantation business. Nurseries are the beginning of efforts to cultivate palm plants, so the nurseries must consider all the conditions that can affect the development of the growth of oil palm plants. One important requirement is to conduct nurseries that tend to be organic, which are environmentally friendly. The use of organic fertilizers and sustainable biological fertilizers is very important in increasing soil fertility, growth and crop yields. Organic fertilizer that used is sugar mill wasted blotong and biological fertilizer is mychorrhizal. To determine the effect of giving sugar mill waste blotong and mycorrhizal applications on P nutrient levels in the Main Nursery. This study uses factorial randomized block design method (RAK). First factor is blotong (B): B0= control, B1= 500 gr blotong/seed, B2= 100 gr blotong/seed. Second factor is Mycorrhizal (M): M0= control, M1= 10 gr mycorrhizal arbusculae/seed, M2= 20 gr mycorrhizal arbusculae/seed. 9 treatment combinations were obtained with 4 replications, so the total treatment was 36. Blotong compost application significantly affected palm seed height, canopy dry weight and root dry weight, while mycorrhizal application only significantly affected seed height. the combination between them two gives the best effect on B1M1 treatment.